2014
DOI: 10.12697/poa.2014.23.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Digit ratio and laterality indices: the Chuvashian study

Abstract: The aim of the present study was to evaluate the association between digit ratio indices (representing the prenatal androgen and estrogen exposure) and different laterality indices, handedness (HDD), the dominant eye (DE), hand clasping (HCL) and arm folding (ARMF) in a large (N=1,586) Chuvashian population-based sample.HDD showed a significant association with the right phalangeal length ratio, the right and the left metacarpal ratio and the right ray ratio. Subjects with a right dominant hand had lower right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It has been proposed that this indicates the level of exposure (and/or sensitivity) to prenatal testosterone (Brown et al, 2002;Manning et al, 1998;Ventura et al, 2013) or the ratio of prenatal testosterone to estradiol (Lutchmaya et al, 2004;Manning, 2011;Zheng and Cohn, 2011). Some studies have reported left-handedness to be associated with male-typical patterns of digit ratio (e.g., Beaton et al, 2011;Fink et al, 2004;Manning and Peters, 2009;Manning et al, 2000;Nicholls et al, 2008;Stoyanov et al, 2011;Stoyanov et al, 2009;Swami et al, 2013;Voracek et al, 2006), others with female-typical patterns (e. g., Baker et al, 2013;Gillam et al, 2008;Jackson, 2008;Kalichman et al, 2014;Ypsilanti et al, 2008), and yet others with no effect at all (e. g., Bescós et al, 2009;Boets et al, 2007;Papadatou-Pastou and Martin, 2017). A meta-analysis of published and unpublished literature (Richards et al, in press) reported negligible effect size estimates (all unsigned point estimates r < 0.060) that were not consistent in direction.…”
Section: Studies Of Prenatal Testosterone and Handednessmentioning
confidence: 99%
“…It has been proposed that this indicates the level of exposure (and/or sensitivity) to prenatal testosterone (Brown et al, 2002;Manning et al, 1998;Ventura et al, 2013) or the ratio of prenatal testosterone to estradiol (Lutchmaya et al, 2004;Manning, 2011;Zheng and Cohn, 2011). Some studies have reported left-handedness to be associated with male-typical patterns of digit ratio (e.g., Beaton et al, 2011;Fink et al, 2004;Manning and Peters, 2009;Manning et al, 2000;Nicholls et al, 2008;Stoyanov et al, 2011;Stoyanov et al, 2009;Swami et al, 2013;Voracek et al, 2006), others with female-typical patterns (e. g., Baker et al, 2013;Gillam et al, 2008;Jackson, 2008;Kalichman et al, 2014;Ypsilanti et al, 2008), and yet others with no effect at all (e. g., Bescós et al, 2009;Boets et al, 2007;Papadatou-Pastou and Martin, 2017). A meta-analysis of published and unpublished literature (Richards et al, in press) reported negligible effect size estimates (all unsigned point estimates r < 0.060) that were not consistent in direction.…”
Section: Studies Of Prenatal Testosterone and Handednessmentioning
confidence: 99%